Impaired pancreatic β-cell compensatory function in Chinese patients with type 2 diabetes and high genetic risk: a 9-year prospective cohort study. (November 2016) - Yan, Jing; Peng, Danfeng; Jiang, Feng; Zhang, Rong; Hu, Cheng; Jia, Weiping
Abstract: Background: Several prospective studies have shown that a genetic risk score combining multiple loci could predict incident type 2 diabetes in white people, but few studies elucidated the underlying mechanism. We aimed to assess the combined effects of type 2 diabetes risk variants on predicting deterioration of blood glucose tolerance, and progressive changes in β-cell function and insulin sensitivity in a prospective cohort in the Chinese population. Methods: We constructed a weighted genetic risk score model based on 40 variants associated with type 2 diabetes validated in an established cross-sectional Chinese population (n=6822). The weighted genetic risk score was categorised into tertiles (low risk<43·0, intermediate risk ≤43·0 to <46·7, high risk ≥46·7) to assess the score's predictive effect on incidence of type 2 diabetes and impaired glucose regulation, as well as changes in Stumvoll first and second phase insulin secretion indices, and Gutt's insulin sensitivity index. We used a community-based prospective cohort by recruiting participants from the Shanghai region of China, including participants with normal glucose tolerance and patients with impaired glucose regulation at baseline. We analysed the data using logistic, Cox, and multiple linear regression tests. Ethical approval was granted by the Institutional Review Board of Shanghai Jiao Tong University Affiliated Sixth People's Hospital. Informed patient consent was given by all participants. Findings: The study commenced in 1998–99 with the enrolment of 2495 individuals at baseline, including 2192 individuals with normal glucose tolerance and 303 with impaired glucose regulation. Individuals were also invited to participate in another two follow-up examinations in 2002–03 and 2010–12. Over an average follow-up of 9·0 (SD 2·8) years, 260 individuals developed type 2 diabetes and 326 individuals developed impaired glucose regulation. The weighted genetic risk score as a ranked variable predicted incidence of type 2 diabetes and impaired glucose regulation in the logistic regression (odds ratio 1·24, 95% CI 1·10–1·39, p=0·0004) as well as in the Cox model (hazard ratio 1·13, 95% CI 1·03–1·24, p=0·013) after adjusting for age, sex, BMI, and smoking and alcohol status at baseline. Moreover, multiple linear regression revealed that the weighted genetic risk score as a ranked variable had a predictive effect on deterioration of β-cell function (β −0·0480 for first phase insulin secretion, and β −0·0303 for second phase insulin secretion, p<0·0001) but not insulin sensitivity (p=0·38) during the 9 year follow-up period. Only individuals in the lowest group had elevated first and second phase insulin secretion, which compensated for impaired insulin sensitivity. However, individuals in the other two groups had decreased first-phase insulin secretion accompanied by increased second-phase secretion to partly offset the initial low levels. Interpretation: The weighted genetic risk score predicted deterioration of blood glucose control through effects on β-cell function in this Chinese population. Individuals in the intermediate weighted or high weighted genetic risk score group showed progressive deterioration of β-cell function. Funding: National Science Foundation of China, the National 863 programme, the National 973 programme, the National Program for Support of Top-notch Young Professionals, Shanghai Municipal Education Commission—Gaofeng Clinical Medicine Grant Support, and the Shanghai Jiao Tong Medical and Engineering Foundation.